EVALUATION OF POLICY INTEGRATION IN THE URBAN-RURAL LOGISTICS SYSTEM: ANALYSIS OF THE NATIONAL LOGISTICS SYSTEM IN INDONESIA - Heliantina, Farah; Maksum, Irfan Ridwan; Prasetyo, Umanto Eko (Ridwan Institute, 2024)
This study aims to provide empirical evidence on the effectiveness of the concept of policy integration from Cejudo and Michel (2017) in the context of rural-urban logistics systems in Indonesia. The study employs a qualitative approach and post-positivism paradigm to clarify the definition and distribution of responsibilities for handling complex problems by various ministries or agencies. The analysis identifies significant disparities in responsibilities and resources among various ministries handling key logistics drivers. This study provides a comprehensive analytical framework that helps to understand how the logistics system can be optimized through better policy integration, more effective inter-agency coordination, and the development of comprehensive strategies, reassuring you of the thoroughness of our approach and its direct relevance to your goals. The results show that effective policy integration and strategic resource allocation are not just important, but urgent for optimizing Indonesia's logistics system, enhancing economic competitiveness, and supporting sustainable development.